Global Positioning System (GPS) Positioning Errors During Ionospheric Scintillation Event - Ho, Yih Hwa; Abdullah, Sabirin; Mohtar, M.H (Universiti Teknologi Malaysia, 2014)
As technology advancement progresses throughout the years in this modern age, every technology has its part to play in that the world is moving towards a brighter future. GPS (Global Positioning System) has diverse application in current globalized world, its application has pervasive benefits not only to navigation and positioning, it is pivotal in industries like logistics, shipping, financial services and agriculture. Since the decision to shut down the Selectivity Availability (SA) by former U.S. President, Bill Clinton, ionospheric effect is now the primary concern of error contributing factors in GPS. Ionospheric scintillation induces rapid fluctuations in the phase and the amplitude of received Global Navigation Satellite System (GNSS) signals. These rapid fluctuations or scintillation potentially introduce cycle slips, degrade range measurements, and if severe enough lead to loss of lock in phase and code. Global Ionospheric Scintillation Model (GISM) was used to compute amplitude scintillation parameter for each GPS satellite visible from Melaka, Malaysia (Latitude 20 14’ N, Longitude 1020 16’ E) as its location has strong equatorial scintillation behavior. The output data from GISM was then used to calculate the positioning error where it is depends on the Dilution of Precision (DOP) and User Equivalent Range Error (UERE). There are two schemes that were used. First, the positioning error was calculated for all the visible satellites with better DOP but worse UERE due to scintillation event. Secondly, the positioning error was calculated for those satellites that have amplitude scintillation index, S4 < 0.7 which leads to worse DOP with better UERE. Comparison of results from the both schemes was then made.